APPLYING SEM-EDX TECHNIQUES TO IDENTIFYING THE TYPES OF MINERAL OF JADES (GIOK) TAKENGON, ACEH - Julinawati .; Marlina .; Rosnani Nasution; Sheilatina . (Jurnal Natural, 2015)
Research on the applying of SEM-EDX techniques for identification of minerals types of Jades (Giok) Takengon Aceh has been done within this study. Based on data of SEM-EDX, it showed that Jades (Giok) Takengon is belonging to a mineral of silicate. The types of minerals of Jades (Giok) Takengon are Grossular (Ca3Al2(SiO4)3 from the Garnet group, which is a mineral of nesosilicate and the other typeÂ  is lizardite, (Mg3Si2O5(OH)4, from the group Serpentine , which is a mineral of phyllosilicate. SEM-EDX can be used as a technique to identify the types of minerals and the results obtained fast and accurate.